East European managers and Western management theories: An ethnographic approach of Romanian service sector enterprises - Monika Heintz (Journal for East European Management Studies, 2002)
This paper addresses the values and beliefs behind the actions of Romanian managers in the field of human resource management, by situating them in their societal/national culture. The paper aims to explain why some managerial actions, inspired by Western management theories, threaten business performance. Despite the development of theories regarding cross-cultural knowledge transfer, the practice of managers in Eastern Europe suggests either a native understanding of knowledge transfer between Western and East European organisations, or an intended deformation/play on Western managerial advice in their own benefit. – – Der Beitrag adressiert die Werte und Überzeugungen, die hinter den Handlungen rumänischer Manager im Bereich des Personalmanagements stehen. Diese werden dabei in ihren gesellschaftlichen/nationalen, kulturellen Kontext verortet. Der Aufsatz will erklären, warum einige, durch westliche Managementkonzepte inspirierte Managementprozesse, die Geschäftsleistung beeinflussen. Trotz der Entwicklung von Theorien zum interkulturellen Wissenstransfer, zeigt die Praxis von Managern in Osteuropa entweder ein naives Verstehen des Wissenstransfers zwischen west- und osteuropäischen Organisationen oder eine beabsichtigte Änderung der westlichen Betrachtungsweise zu ihrem eigenen Vorteil.
Keywords: 650